A case of Metaplastic atrophic gastritis in immune Dysregulation, Polyendocrinopathy, Enteropathy, X-linked (IPEX) syndrome - Youyou Luo; Jie Chen; Youhong Fang; Jingan Lou; Jindan Yu (BMC, 2018)
Abstract Background Autoimmune metaplastic atrophic gastritis is a chronic progressive inflammatory condition. The clinical spectrum includes pernicious anemia, atrophic gastritis, antibodies to parietal cell antigens and intrinsic factor, achlorhydria, hypergastrinemia and carcinoma. It is rare in paediatric cohorts. Case presentation We present the case of a boy with metaplastic atrophic gastritis in whom immune dysregulation, polyendocrinopathy, enteropathy, X-linked(IPEX) syndrome was confirmed by FOXP3 gene mutation. The patient was referred to the hospital at the age of 3 years with recurrent emesis, diarrhoea and malnutrition. His elder brother died at 9 years of age from acute respiratory distress syndrome and renal tubular acidosis. The patient was allergic to cow milk formula and noodles. Oesophagegastroduodenoscopy revealed redness, erosion and edema throughout the stomach; whitish granules in the duodenal bulb; and edema in the second part of the duodenum. Biopsies showed extensive villous atrophy and goblet cell depletion in the duodenum. He was diagnosed with type-1 diabetes mellitus (T1DM) during the treatment of methylprednisolone. Serum antibodies against glutamic acid decarboxylase and pancreatic islets were detected. The patient's FOXP3 gene was sequenced; this identified that the patient was hemizygous for a pathogenic variant [NM_014009.3:c.748_750del (p.Lys250del)]. Conclusion Metaplastic atrophic gastritis is rarely reported in patients with IPEX. Clinical gastroenterologists should be aware of IPEX syndrome when facing the complex syndromes of metaplastic atrophic gastritis and endocrinopathy.